2015
DOI: 10.2460/ajvr.76.6.487
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of glycerol, dimethyl sulfoxide, and hydroxyethyl starch solutions for cryopreservation of avian red blood cells

Abstract: Cryopreservation of avian RBCs with HES solution, regardless of HES concentration, resulted in greater degrees of apoptosis and cell death than did cryopreservation with other media. Transfusion with RBCs cryopreserved in HES solution may result in posttransfusion hemolysis in birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…The authors speculated that the low recovery rate could be due to small details in their protocol, including the addition rate of each aliquot of glycerol, time allowed for equilibration of glycerol with the RBCs, freezing rate of the samples or the deglycerolization process. 25 Another issue with glycerol cryopreservation encountered in our study was the unexpected agglutination during the glycerol wash steps in the feline samples. To rule out agglutination caused by removal of the anticoagulant during the wash steps, we added back anticoagulant to unit #4 both before the first washing steps (aliquot 2) and after the second wash (aliquot 3).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors speculated that the low recovery rate could be due to small details in their protocol, including the addition rate of each aliquot of glycerol, time allowed for equilibration of glycerol with the RBCs, freezing rate of the samples or the deglycerolization process. 25 Another issue with glycerol cryopreservation encountered in our study was the unexpected agglutination during the glycerol wash steps in the feline samples. To rule out agglutination caused by removal of the anticoagulant during the wash steps, we added back anticoagulant to unit #4 both before the first washing steps (aliquot 2) and after the second wash (aliquot 3).…”
Section: Discussionmentioning
confidence: 89%
“…18 A manual technique for glycerolization and deglycerolization was also employed in a study of cryopreservation of avian red blood cells. 25 The avian study reported a recovery rate of 0% after the washing steps. The authors speculated that the low recovery rate could be due to small details in their protocol, including the addition rate of each aliquot of glycerol, time allowed for equilibration of glycerol with the RBCs, freezing rate of the samples or the deglycerolization process.…”
Section: Discussionmentioning
confidence: 99%
“…After sampling, six aliquots of whole blood (25 μl) per bird were created and 75 μl of freezing media (10% dimethyl sulfoxide [DMSO], 60% fetal bovine serum, and 30% modified Eagle medium‐α; Graham, Meola, Kini, & Hoffman, 2015) was added to each tube. Note that there are many cryopreservation methods and the one used here was based on one previously published method of avian red blood cell preservation (Graham et al, 2015). Three aliquots were then stored at −20°C and the other three aliquots were first slowly frozen to −80°C by surrounding the vials with isopropyl alcohol enclosed in a Styrofoam container overnight, then transferred to LN2.…”
Section: Methodsmentioning
confidence: 99%
“…The advantages of cryopreservation methods with non-penetrating cryoprotectants for RBCs include the possibility to eliminate the washing steps prior to transfusion. However, the drawback of such CPAs is the presence of latent damage in thawed erythrocytes, which manifests itself in lowering the osmotic stability when they are placed in isotonic medium [24,25]. …”
Section: Introductionmentioning
confidence: 99%